Machine Learning-Assisted Low-Dimensional Electrocatalysts Design for Hydrogen Evolution Reaction - Li, Jin; Wu, Naiteng; Zhang, Jian; Wu, Hong‑Hui; Pan, Kunming; Wang, Yingxue; Liu, Guilong; Liu, Xianming; Yao, Zhenpeng; Zhang, Qiaobao (Nano-Micro Letters, 2023)
Efficient electrocatalysts are crucial for hydrogen generation from electrolyzing water. Nevertheless, the conventional "trial and error" method for producing advanced electrocatalysts is not only cost-ineffective but also time-consuming and labor-intensive. Fortunately, the advancement of machine learning brings new opportunities for electrocatalysts discovery and design. By analyzing experimental and theoretical data, machine learning can effectively predict their hydrogen evolution reaction (HER) performance. This review summarizes recent developments in machine learning for low-dimensional electrocatalysts, including zero-dimension nanoparticles and nanoclusters, one-dimensional nanotubes and nanowires, two-dimensional nanosheets, as well as other electrocatalysts. In particular, the effects of descriptors and algorithms on screening low-dimensional electrocatalysts and investigating their HER performance are highlighted. Finally, the future directions and perspectives for machine learning in electrocatalysis are discussed, emphasizing the potential for machine learning to accelerate electrocatalyst discovery, optimize their performance, and provide new insights into electrocatalytic mechanisms. Overall, this work offers an in-depth understanding of the current state of machine learning in electrocatalysis and its potential for future research. Highlights: 1 The process of machine learning is introduced in detail. 2 Recent developments in machine learning for low-dimensional electrocatalysts are briefly reviewed. 3 Future directions and perspectives for machine learning in hydrogen evolution reaction are critically discussed.